The foetus, a surgical patient - Calisti, Alessandro (Medicina e Morale, 2024)
The 1970s saw a rapid growth of interest in the medical field in the prenatal diagnosis of congenital malformations. Among these, the incidence rate of pathology susceptible to surgical correction or otherwise requiring an operative act to allow survival or a satisfactory quality of life is much higher than is commonly thought.